Research of modes and work of a combined unit for subsoil application of protective-stimulating liquids in spaces between rows of gardens and vineyards - Borisova Svetlana M.; Papusha Sergey K.; Papusha Vladimir K.; Nikitenko Nikolay A. (MATEC Web of Conferences, 2019)
The combined unit is used for tillage and subsurface belt application of protective and stimulating liquids and microorganisms into the soil. New technology offers for the task to use pneumatic slotted sprayers with jet-forming device that is linked with a compressor that delivers air to transform the operation fluid from the tank in the aerial-droplet jet processing lower layers of the soil simultaneously with cultivation. Protective shields save the sprayer from deformation and breakage. To obtain the required range of the jet, the angle of inclination of the sprayer is adjusted. The supply line of operation fluid has an equalizing capacity to change the flow rate of the operation fluid. The basis of the development of sprayers was the task of development of a plane-parallel jet capable of spreading to a distance to 2 m with an adjustable width of a grip m/s. there were conducted the researches of performance (charge) of pneumatic slotted sprayer depending on air pressure given to in slotted nozzles of the sprayer.